Polar Properties and Hysteresis Loops in Multilayered Thin Films Ferroelectric/Virtual Ferroelectric - Eliseev, E.A.; Glinchuk, M.D.; Morozovska, A.N.; Yakovenko, Ya.V. (Ukrainian Journal of Physics, 2021)
In the framework of Landau–Ginzburg–Devonshire (LGD) phenomenological theory, the influence of misfit strains, surface energy, and finite-size effects on phase diagrams, polar properties, and hysteresis loops has been calculated for multilayered thin films of the type ferroelectric/virtual ferroelectric. The influence of elastic deformations that arise at the interface thin film–substrate owing to a mismatch between the lattice constants in the film and the substrate on the phase diagrams of multilayered thin films virtual ferroelectric SrTiO3/ferroelectric BaTiO3 has been studied for the first time. In contrast to bulk BaTiO3, in which only four phases (cubic, tetragonal, orthorhombic, and rhombohedral) can exist, it turned out that six thermodynamically stable BaTiO3 phases (paraelectric phase and tetragonal (FEc), two monoclinic (FEaac and FEac), and two orthorhombic (FEa and FEaa) ferroelectric phases) can exist in multilayered SrTiO3/BaTiO3 films. The main polar properties of hysteresis loops (shape, coercive field, and spontaneous polarization) in thin multilayered SrTiO3/BaTiO3 films are calculated. It is shown that the system demonstrates a strong dependence of its polar properties on the thickness of SrTiO3 and BaTiO3 layers, as well as on the elastic misfit strains, with SrTiO3 playing the role of dielectric layer: the thicker the layer, the stronger is the depolarization field, which, in its turn, reduces the spontaneous polarization in the BaTiO3 film.